Electrochemical Properties of MnOx-RuO2 Nanofiber Mats Synthesized by Co-Electrospinning - Hyun, Tae-Seon; Kang, Ji-Eun; Kim, Ho-Gi; Hong, Jae-Min; Kim, Il-Doo (ELECTROCHEMICAL SOC INC, 2009)
We report on the fabrication and characterization of layer-by-layer stacked MnOx-RuO2 nanofiber mats via co-electrospinning and their potential application for electrochemical capacitors. The morphology of multistacked MnOx-RuO2 fiber mats provides high porosity for the efficient permeability of electrolyte into the inner structure while maintaining a high surface area for enhanced surface activity. In an electrochemical capacitor using MnOx-RuO2 fiber mats, MnOx offers a facile ion pathway and RuO2 provides a fast electron pathway. The electrochemical capacitors utilizing co-electrospun MnOx-RuO2 fiber mats exhibited a high specific capacitance of 208.7 F/g at 10 mV/s. (C) 2009 The Electrochemical Society. [DOI:10.1149/1.3224899] All rights reserved.
Keywords: CHARGE STORAGE MECHANISM; MNO2; SUPERCAPACITOR; BEHAVIOR; ELECTRODE